The Faktor Risiko Penggunaan Media Sosial pada Obesitas - Ratu Henggar Audrya Gharrieni; Dian Isti Angraini; Fidha Rahmayani (Medula, 2023)
Obesity has become one of the global health problems in the last decade due to the increasing likelihood of various diseases that can reduce quality of life. The prevalence of obesity in the world reached 1 billion in 2022, and an estimated 167 million people will have the health problems due to obesity. One of the factors that contribute to the incidence of obesity is social factors, it can affect individual lifestyles such as excessive food consumption and high calories, increased social media usage behavior so that physical activity decreases and can cause obesity. Some individuals tend to spend their time using social media with smartphones, tablets, laptops or computers which are thought to increase the risk. This article aims to determine whether the use of social media can increase the incidence of obesity in individuals and determine the effect on the incidence of obesity. Based on the literature review conducted, social media used can be a factor that increases the risk of obesity, especially if the intensity of social media used is high, because it can have an impact on individual health  in poor consumption behavior and disturbed sleep quality which can be a risk factor for obesity.